Preservıce Teachers’ Opinions on the Use of Technology in Education - Nazgul, Kozhamkulova; Anar, Bukhaeva; Baglan, Zharapova; Moldir, Seidina; Sadvakasova, Gulbanu; Nishanbayeva, Sabira (International Journal of Emerging Technologies in Learning (iJET), 2020)
Educational technologies have become more important especially in the recent years. The use of technology to facilitate learning has increased over the past decade, but relevant problems in education are still on the agenda. The aim of this study is to determine the opinions of preservice teachers about using technological tools in education. Qualitative method was used in the study. The study was applied to the 32 senior students studying at the classroom teaching department of a university in Kazakhstan. Data were collected with interviews. The interview questions were prepared to get the opinions of preservice teachers studying in the classroom teaching department regarding the use of technology in educational technology, and the questions were applied by giving the final shape by the experts in their fields. According to the results, preservice teachers feel insufficient to use the internet and computer for teaching purposes. However, they stated that they are sufficient in using computers and internet search engines, they can prepare simple materials for teaching purposes and they can not prepare multi-purpose teaching devices. This difference can be overcome with individual research and project assignments that require preservice teachers to use technology for teaching purposes.